Biventricular or left univentricular pacing in heart failure patients: is there a better strategy. (3rd October 2022) - Barradas, M; Duarte, F; Coutinho Dos Santos, I; Resendes De Oliveira, L; Serena, C; Xavier Fontes, A; Viveiros Monteiro, A; Machado, C; Dourado, R; Santos, E; Pelicano, N; Pacheco, M; et al.
Abstract: Background: Cardiac resynchronization therapy (CRT) is a cornerstone in treatment of heart failure (HF) with reduced left ventricular ejection fraction (LVEF) and ventricular dyssynchrony. Biventricular (BiV) pacing is often the preferred method and corrects electrical and mechanical dyssynchrony but Left ventricular (LV) preferential pacing is may preserve conduction via the right bundle branch, preventing deleterious effects from right ventricular. The evidence is sparse and there is doubts whether which programming strategy is better. Purpose: We hypothesized that BiV is non-inferior to preferential LV pacing in HF patients with reduced LVEF and CRT devices in cardiovascular death and HF hospitalizations. Methods: We retrospectively evaluated 147 patients with HF patients with reduced LVEF and CRT devices. Two groups were defined: LV pacing (group 1) and BiV pacing (group 2). Primary outcome was defined as cardiovascular death and secondary outcome as HF hospitalizations and NYHA class after CRT. Results: Mean age was 70, 26±10, 6 years, 68, 1% were males and follow-up was 52, 22±44, 51 months. One hundred and twenty six (85, 7%) patients had implantable cardiac resynchronization therapy (CRT) defibrillator (CRT-D) and 21 (14, 3%) CRT pacemaker (CRT-P). Mean LVEF was 31, 1±8, 5% and mean QRS duration before CRT implantation was 149, 5±48, 6 ms. Thirty-nine (36, 4%) patients were in NYHA III–IV. HF aetiology was idiopathic in 51 (47, 2%), ischemic in 36 (33, 3%) and alcoholic cardiomyopathy in 9 (8, 3%). Forty-five (40, 5%) patients had atrial fibrillation and 37 (35, 6%) coronary disease. Patients in group 2 were more frequently males than group 1 patients (46 (78, 0%) vs 32 (56, 1%) respectively, p=0, 012). There were no differences in regard to age, LVEF, HF aetiology or other comorbidities between groups. In 57 (49, 1%) CRT was programming in preferential LV pacing and 50 (50, 9%) in BiV pacing. There were 2 deaths in group 1 and 3 in group 2 (OR 0.80, 95% CI 0.27–2.40). There were 0, 98±3, 17 hospitalizations per patient and there were no differences in HF hospitalizations between groups (OR 1.01, 95% CI 0.92–1.18) or NYHA after 6 months of CRT (p=0, 364). Conclusion: BiV pacing was not inferior to LV-only pacing in regard to cardiovascular death, HF hospitalizations and NYHA class improvement. There was no clear advantage for one pacing strategy over the other but more studies are still required. Funding Acknowledgement: Type of funding sources: None.